Vote for Whom : Voting Behavior of Thailand’s House of Representatives - pankaew, attasit (King Prajadhipok’s Institute Journal, 2020)
This article aims to study the voting behaviors of members of Thailand’s House of Representatives, focusing on the question, “for whom” do these people vote during the legislative process and when considering other issues. The research employs mixed research methods; empirical data is analyzed and then the results are integrated with data collected through in-depth interviews. The scope of this research is limited to the information about voting by the members of the House of Representatives under study during the twentieth House of Representatives (1998 under the Chuan Leekpai government) to the dissolution of the twenty-fourth (2013 under the Yingluck Shinawatra government). From three main theorized patterns (party-line voting, coalition–line voting, and cross party–line voting), it was found that (1) the statistical value of the party loyalty score of individual members of the House of Representatives in different periods is higher than 90%, showing that most of the members of the House of Representatives vote in line with their parties’ resolutions and majority opinions; (2) Thai political parties are straight coalition-line voters (government-opposition-line voting); and (3) cross party-line voting behaviors are noticeable with the smaller parties, specifically that they will vote in the same line as a big party on the government side.